Evaluation of the 3D spatial distribution of the Calcium/Phosphorus ratio in bone using computed-tomography dual-energy analysis. Issue 1 (January 2016) - Hadjipanteli, A.; Kourkoumelis, N.; Fromme, P.; Huang, J.; Speller, R.D.
Highlights: We test a CT technique for Ca/P ratio assessment in bone apatite. We extend the technique for its application to intact bone. Differences in Ca/P ratio are found between healthy and osteoporotic bones. Potential in vitro and in vivo applications of the technique are described. Abstract: Purpose: The Calcium/Phosphorus (Ca/P) ratio was shown to vary between healthy bones and bones with osteoporotic symptoms. The relation of the Ca/P ratio to bone quality remains under investigation. To study this relation and determine if the ratio can be used to predict bone fractures, a non-invasive 3D imaging technique is required. The first aim of this study was to test the effectiveness of a computed-tomography dual-energy analysis (CT-DEA) technique developed to assess the Ca/P ratio in bone apatite (collagen-free bone) in identifying differences between healthy and inflammation-mediated osteoporotic (IMO) bones. The second aim was to extend the above technique for its application to a more complex structure, intact bone, that could potentially lead to clinical use. Methods: For the first aim, healthy and IMO rabbit cortical bone apatite samples were assessed. For the second aim, some changes were made to the technique, which was applied to healthy and IMO intact bone samples. Results: Statistically significant differences between healthy and IMO bone apatite were found for the bulk Ca/P ratio, low Ca/P ratio proportion and interconnected low Ca/P ratio proportion. For the intact bone samples, the bulk Ca/P ratio was found to be significantly different between healthy and IMO. Conclusions: Results show that the CT-DEA technique can be used to identify differences in the Ca/P ratio between healthy and osteoporotic, in both bone apatite and intact bone. With quantitative imaging becoming an increasingly important advancement in medical imaging, CT-DEA for bone decomposition could potentially have several applications.